2023
DOI: 10.1002/anie.202217791
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the Elusive “In‐Between” State of the Copper‐Amyloid β Complex by X‐ray Absorption through Partial Thermal Relaxation after Photoreduction

Abstract: The redox activity of Cu ions bound to the amyloid‐β (Aβ) peptide is implicated as a source of oxidative stress in the context of Alzheimer's disease. In order to explain the efficient redox cycling between CuII‐Aβ (distorted square‐pyramidal) and CuI‐Aβ (digonal) resting states, the existence of a low‐populated “in‐between” state, prone to bind Cu in both oxidation states, has been postulated. Here, we exploited the partial X‐ray induced photoreduction at 10 K, followed by a thermal relaxation at 200 K, to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Some of the authors of the present paper recently exploited this idea to acquire an XAS spectrum of a species generated by X‐ray induced photoreduction of Cu(II)‐A β at 10 K. As at 10 K only a minimal structural reorganization is possible, [42] a partial thermal relaxation at 200 K was performed. Noteworthy, the XAS spectrum measured after the annealing is different from the resting states of both Cu(I) and Cu(II)‐A β , and was found to be compatible with a proposed model of IBS, as sketched in panel c) of Figure 2 [36] …”
Section: Alzheimer's Disease and Cu‐aβ Complexessupporting
confidence: 65%
See 1 more Smart Citation
“…Some of the authors of the present paper recently exploited this idea to acquire an XAS spectrum of a species generated by X‐ray induced photoreduction of Cu(II)‐A β at 10 K. As at 10 K only a minimal structural reorganization is possible, [42] a partial thermal relaxation at 200 K was performed. Noteworthy, the XAS spectrum measured after the annealing is different from the resting states of both Cu(I) and Cu(II)‐A β , and was found to be compatible with a proposed model of IBS, as sketched in panel c) of Figure 2 [36] …”
Section: Alzheimer's Disease and Cu‐aβ Complexessupporting
confidence: 65%
“…Panels a and b: Cu(II) and Cu(I)‐Aβ coordination modes [35] . Panel c: proposed Cu(I)/Cu(II) intermediate state [36] …”
Section: Alzheimer's Disease and Cu‐aβ Complexesmentioning
confidence: 99%
“…ROS production is mediated by the redox cycling between the Cu(II) and Cu(I) oxidation states occurring in the presence of ascorbate. Recently, it has been shown that ROS production is catalyzed by a low-populated copper binding state, different from the Cu(II) and Cu(I) binding modes observed in the "resting state" [64].…”
Section: Discussionmentioning
confidence: 92%
“…However, involvement of residues through the intermediate sites may precede redox activities in Cu II :A� complexes. A comprehensive study of intermediate-site structure during reductions can be performed using XAS-EC and the highenergy fluorescence detection (Shearer & Szalai, 2008;Arrigoni et al, 2018;Falcone et al, 2023) approach in future.…”
Section: Discussionmentioning
confidence: 99%